Permendag Analysis Number 18 year 2021 Related to the Sale and Purchase of Imported Used Clothing Trade - Elfrida Ratnawati Gultom; Ibrahim Satyanegara (IHSA Institute, 2022)
Buying and selling imported used clothing is a form of transaction with clothing objects from outside Indonesia and mostly carried out by the public. Meanwhile, the Government has banned the sale and purchase transaction of imported used clothes because one of the activities violates and greatly deviates from the applicable laws and regulations. The import trade itself has also been regulated in